Income Smoothing Practices in Animal Feed Sub-Sector Companies Listed on the Indonesia Stock Exchange For the 2020-2022 Period - Junita Nur Afiffah; Boyke Martin; Devi Ramadhaningsih; Binsar Samuel; Yanuar Ramadhan; Muhammad Atthariq (Mutiara: Multidiciplinary Scientifict Journal, 2023)
This study aims to analyze Income Smoothing practices in animal feed sub-sector companies with a focus on the financial implications of using the eckel index during the period 2020 – 2022. The sample used is animal feed sub-sector companies in the basic industrial and chemical sectors listed on the Indonesia Stock Exchange, there are 5 companies. Based on calculations using the eckel index derived from the financial statements of each company, This research shows that there are 4 companies that do profit smoothing and 1 company that does not do income smoothing.